Molecular Signaling Mechanisms and Function of Natriuretic Peptide Receptor-A in the Pathophysiology of Cardiovascular Homeostasis - Pandey, Kailash N. (Frontiers in Physiology, 2021)
The discovery of atrial, brain, and C-type natriuretic peptides (ANP, BNP, and CNP) and their cognate receptors has greatly increased our knowledge of the control of hypertension and cardiovascular disorders. ANP and BNP are potent endogenous hypotensive hormones that elicit natriuretic, diuretic, vasorelaxant, antihypertrophic, antiproliferative, and antiinflammatory effects, which are important in the control of blood pressure (BP) and cardiovascular homeostasis. The principal receptor involved in the regulatory actions of ANP and BNP is guanylyl cyclase/natriuretic peptide receptor-A (GC-A/NPRA), which produces the intracellular second messenger cGMP. Cellular, biochemical, molecular, genetic, and clinical studies have facilitated understanding of the functional roles of natriuretic peptides (NPs), as well as the functions of their receptors, and signaling mechanisms in cardiovascular homeostasis. Transgenic and gene-targeting (gene-knockout and gene-duplication) strategies have produced genetically altered novel mouse models and have advanced our knowledge of the importance of NPs and their receptors at physiological and pathophysiological levels in both normal and disease states. The current review describes the past and recent research on the cellular, molecular, genetic mechanisms and functional roles of the ANP-BNP/NPRA system in the physiology and pathophysiology of cardiovascular homeostasis as well as clinical and diagnostic markers of cardiac disorders and heart failure. However, the therapeutic potentials of NPs and their receptors for the diagnosis and treatment of cardiovascular diseases, including hypertension, heart failure, and stroke have just begun to be expanded. More in-depth investigations are needed in this field to extend the therapeutic use of NPs and their receptors to treat and prevent cardiovascular disorders.